2019
DOI: 10.1155/2019/5484138
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Citrus Flavonoids on Cardiovascular and Metabolic Health

Abstract: The prevalence of cardiovascular disease (CVD) is increasing over time. CVD is a comorbidity in diabetes and contributes to premature death. Citrus flavonoids possess several biological activities and have emerged as efficient therapeutics for the treatment of CVD. Citrus flavonoids scavenge free radicals, improve glucose tolerance and insulin sensitivity, modulate lipid metabolism and adipocyte differentiation, suppress inflammation and apoptosis, and improve endothelial dysfunction. The intake of citrus flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(161 citation statements)
references
References 187 publications
(251 reference statements)
1
129
0
2
Order By: Relevance
“…WHO reports that, more than 60% of the societies in lowincome countries rely upon medicinal plants for their primary health care because of their easy accessibility, low cost and minimal adverse effects. 15 Over the years, scientists have been researching on food and plant products that possess protective effects against cardiac injury. It was discovered that diets rich in natural antioxidants (especially flavonoids) have potent effects against oxidative stress caused by cardiotoxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…WHO reports that, more than 60% of the societies in lowincome countries rely upon medicinal plants for their primary health care because of their easy accessibility, low cost and minimal adverse effects. 15 Over the years, scientists have been researching on food and plant products that possess protective effects against cardiac injury. It was discovered that diets rich in natural antioxidants (especially flavonoids) have potent effects against oxidative stress caused by cardiotoxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are a kind of natural polyphenols, mainly including flavonoids, flavanols, flavonoids, anthocyanins, and isoflavones [225]. Studies had shown that flavonoids had definite efficacy in the treatment of agerelated neurodegenerative diseases [226], cardiovascular diseases [227,228], atherosclerosis [229], etc. Some progress has Modulation of the mitochondrial pathway of apoptosis and the cholinergic system [186] 12…”
Section: Flavonoidsmentioning
confidence: 99%
“…Free radicals which are formed during normal cellular metabolism cause oxidative stress when there is an imbalanced defense mechanism by antioxidants. Flavonoids are known free radical scavengers as they exhibit several biological activities such as anti-inflammatory, antioxidant, and immunomodulatory, hence, are found to be effective scavengers of oxidizing molecules, thereby lowering formation of free radicals [16]. Hence, Kokilaksham kashayam fractions which showed the presence of a wide range of phytochemicals were analyzed for their ability to scavenge free radicals such as DPPH, ABTS, and NO.…”
Section: Merlin and Kumarmentioning
confidence: 99%